Biblical discourse as a technology of "othering": A decolonial reading on the 1840 Moffat sermon at the Tabernacle, Moorfields, London - Mothoagae, Itumeleng D. (HTS teologiese studies, 2022)
In his sermon to the directors of the London Missionary Society (LMS) in London in 1840, in ‘othering’ the Batswana (Africans), Moffat engages in biblical discourse. He uses biblical descriptions to ‘other’ them and the land they occupied. This article analyses the 1840 sermon by Moffat, and in it I will argue that through his sermon, Moffat engaged in biblical discourse and performed epistemic privilege in his exposition of the Batswana to his audience, namely the directors of the LMS. At the same time, he used biblical texts and imagery to create in the mind of his listeners an image of heathenism and uncivility. In doing so, I argue that he further located the Batswana within the realm of the ‘damnés’. In the article, I apply two analytical lenses, namely decoloniality and critical race theory, as hermeneutical tools.Contribution: It is argued in this article that in doing so, Moffat further located the Batswana within the realm of the damnés.